RANCANG BANGUN APLIKASI E-COMMERCE PADA ZAHRA TOYS (Information Technology and Telematics, 2014)
Abstract - Technology has influenced many in the community around them is also in many ways and means. The role of technology in business is the Internet is becoming one of the evidence of current technological developments, business activities through internet technology is commonly referred to as e-commerce. With online sales or e-commerce throughout human on this earth has the opportunity to do business in the virtual world. The final task of web design e-commerce at a doll shop that Zahra Toys aims to facilitate the public in the process of buying or shopping online, especially in the field of shopping doll.Said design e-commerce applications on the store's doll using a methodology Toys Zahra system development life cycle (SDLC) and created using MySQL as a database, PHP and JavaScript as the programming language, and Dreamweaver-8 as an editor. As for the table - a table used in the creation of e-commerce on sale in stores Toys Zahra is a table of objects (barang), shipping table (biayakirim), table counter (counter), tables confirmation (konfirm), tables of customers (pelanggan), table order (tborder), table admin (tbuser), table testimonial (testi), which is where all of these tables will be used to hold all the data that is required in the development of e-commerce websites on Zahra Toys doll store. Keywords: system development life cycle, PHP, design e-commerce applications